The Use of Wall Charts in Instruction to Improve the Eighth Grade Students Vocabulary Mastery (An Experimental Study at SMP Negeri 4 Banda Aceh) - Fitria, Nora; Rafsanjani, T M (Universitas Malikussaleh, 2020)
The study was aimed to find out if there is a significant difference between the eighth grade students of SMP Negeri 4 Banda Aceh who are taught vocabulary by using wall chart and those who are taught without using wall chart. The experiment was from conducted from from March 5th, 2018 to May 8th, 2018. 2018 at SMP Negeri 4 Banda Aceh. This study is conducted by using quantitative research and in this case is an experimental study. The population of this study is all students of the eighth grade students of SMP Negeri 4 Banda Aceh in academic year 2017/2018. The total population is 115 students who are composed of five classes; class VIII1, class VIII2, class VIII3, class VIII4, and class VIII5. While the sample of this study is taken from two classes of the five classes. One class is as an experimental group and one another is as control group. In this study, the students of class VIII5 are taken as experimental group and the students of class VIII4 are taken as control group. Every group consists of 30 students thus the total sample is 60. Choosing class as experimental and control group is done randomly. The data were gotten through test; pre-test and post test. The data were analyzed by using SPSS 18.0. The result of the study shows that there is a significant difference between the eighth grade students of SMP Negeri 4 Banda Aceh who are taught vocabulary by using wall chart and those who are taught without using wall chart. It can be proven from the result of this study where the result of t-test of post-test of the both group is 3.028. While the result of t-table with the level of significance 0,05 is 0,668. Thus, t-test (3.028) is greater than the t-table (0,668). Based on the result of the study, English teachers of SMP Negeri 4 Banda Aceh especially those who teach vocabulary should implement Wall Charts in teaching and learning process because the implementation of the media can increase the students vocabulary mastery.